“Am I a candidate for magic mushrooms?” A mystery shopper study of Oregon psilocybin service centers - Danielle R Adams; Morgan Hartman; Lisa Gong; Suraj Shankar; Ruth Ling; Jacob T Steinle; Joshua S Siegel; Ginger E Nicol; Richard A Grucza; Jacob T Borodovsky; Leopoldo J Cabassa; Kevin Y Xu (Health Affairs Scholar, 2026)
Abstract Introduction Oregon is the first US state to permit supervised psilocybin services through a nonmedical, wellness-based model. We examined what prospective clients with psychiatric histories encounter when contacting service centers, including how staff communicate about safety, eligibility, and cost. Methods We conducted a mystery shopper study of 26 licensed service centers in Oregon (7/2025-9/2025), 4 of which closed before calls began, leaving 22 in the sample. We reviewed websites and conducted two waves of scripted phone calls portraying adults with depression. Website and call data were combined at the center level, counting an item as disclosed if it appeared online or during a call. Themes from call field notes were contextualized through structured debriefing interviews with service center staff. Results Callers reached 15/22 centers, none of which permitted unsupervised consumption or immediate dosing without psychiatric assessment. Staff asked detailed questions about psychiatric comorbidities, addressing information gaps from websites, and none recommended discontinuing antidepressants. The median cost was $1,900. Debriefing interviews described financial strain, with viability constrained by licensing fees and potential misalignment with cannabis-derived business models. Conclusion Oregon’s regulated model appears more clinically cautious than skeptics anticipated, while facing high costs for clients and service center staff that limit scalability.